KOMUNIKASI PARIWISATA DAN KUALITAS PELAYANAN PEMANDU LOKAL SEBAGAI PREDIKTOR KEPUASAN WISATAWAN DI CANDI GEDONG SONGO KABUPATEN SEMARANG - Desta Lina Angriani Laia; Yustina Denik Risyanti (Media Bina Ilmiah, 2025)
The purpose of this investigation is to evaluate the impact of tourism communication and the quality of local guide services on the level of tourist satisfaction at Gedong Songo Temple, Semarang Regency, and to evaluate the impact of tourism communication and the quality of local guide services on the level of tourist satisfaction at Gedong Songo Temple, Semarang Regency together. This study is quantitative research. Primary and secondary data are the two categories of data that are utilized. The instrument used in this research is a questionnaire which was processed using SPSS for Windows 17.0, while the number of samples are 97 respondents. The study's findings include: (1) There's an impact of tourism communication and the quality of local guide services on the level of tourist satisfaction at Gedong Songo Temple, Semarang Regency. (2) There's an impact of tourism communication and the quality of local guide services on the level of tourist satisfaction at Gedong Songo Temple, Semarang Regency simultaneously.